Comparing the Efficacy of Mtwo and D-RaCe Retreatment Systems in Removing Residual Gutta-Percha and Sealer in the Root Canal - Akhavan, Hengameh; Azdadi, Yaser Khalil; Azimi, Shahram; Dadresanfar, Bahare; Ahmadi, Anahid (Iranian Endodontic Journal, 2012)
Introduction: Retreatment is performed in teeth with unsuccessful root canal therapy or persistent apical lesion. The most important factor for achieving successful retreatment is thorough cleaning and reshaping. NiTi files and rotary instruments are widely used for the removal of obturatants. This study compared the ability of Mtwo and D-RaCe retreatment systems to remove residual gutta-percha and sealer within the root canal after retreatment. Materials and Methods: This in vitro experiment was performed on sixty extracted human teeth. The samples were cut at the CEJ level, manually prepared, filled with gutta-percha and AH26 and finally stored at 37ºC for two weeks. Samples were then randomly divided into two groups. Group 1 was retreated with Mtwo and Group 2 with D-RaCe. Both groups were then divided into two subgroups retreated either with or without solvent. Teeth were then vertically sectioned for evaluation of residual filling materials on the canal walls. A microscopic assessment at 16× magnification was performed. T-test statistical analysis was used to compare the data. Results: Comparison between the Mtwo and D-RaCe rotary systems revealed no significant differences in residual gutta-percha or sealer on canal walls (P=0.2). The study revealed a negative effect of solvent on removal of gutta-percha and sealer in both the Mtwo and D-RaCe systems. Conclusion: Mtwo and D-RaCe retreatment files removed residual gutta-percha and sealer similarly; there was no significant difference between them.